Co-producing formulation within a secure setting: a co-authorship with a service user and the clinical team. Issue 4 (14th August 2017) - Lewis-Morton, Ruth; Harding, Sarah; Lloyd, April; Macleod, Alison; Burton, Simon; James, Lee
Abstract : Purpose: The purpose of this paper is to explore the process of co-producing a formulation alongside a service user and the clinical team within a secure inpatient service. This paper has been co-authored by the service user and members of the multi-disciplinary team (MDT). Design/methodology/approach: An open-ended focus group discussion was facilitated with the service user and members of her MDT. The process of thematic analysis was applied to the focus group transcript. Findings: The following themes highlighted important outcomes of co-producing a formulation within a secure inpatient setting; "Meaningful Collaboration", "Co-Produced Understanding" and a "Shift in Power Differential". This paper demonstrates the importance of meaningful co-production within a secure inpatient service whilst also highlighting the challenges and tensions of working in a co-produced way within this context. Research limitations/implications: This paper explores the process of co-producing and developing a formulation from the perspective of one service user and their MDT within a secure inpatient setting. It would be unhelpful to extrapolate broad assumptions from this case study although this study does raise important considerations for future research and encourages an emphasis on a co-produced design and dissemination. Practical implications: This case study highlights the importance of co-production in clinical endeavours, service delivery and development perspectives and in the dissemination of this information. Originality/value: The importance of co-producing and co-authoring alongside service users have been highlighted in this paper. This approach to co-production and co-authorship is highly recommended in future research endeavours.